Strategi Pengelolaan Kas dan Modal Kerja bagi UMKM Tahu Sumedang Boga Rasa - Muhammad Luthfi; Alfina Suci; Cantika Suryani; Devina Safa Yunita; Erin Dwi Juliani; Muhammad Alfinnoor; Tiara Dwi Agustini (Jurnal Kabar Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in supporting the national economy. However, many business owners still face challenges in financial management, particularly in cash and working capital management. These problems were also identified at Tahu Sumedang Boga Rasa MSME located in Langkapura Village, Kemiling District, Bandar Lampung City, where financial records were still maintained in a simple manner, business and personal finances had not been separated, and working capital planning had not been optimally implemented. This Community Service Program (PKM) aimed to improve the business owner's understanding of cash and working capital management to support business sustainability and development. The method used was a descriptive method with a participatory approach through observation, interviews, socialization, mentoring, and evaluation stages. The results showed that prior to the implementation of the program, the partner did not maintain regular financial records and still experienced difficulties in managing cash and working capital. After participating in the socialization and mentoring activities, the partner demonstrated an improved understanding of the importance of recording income and expenses, separating business finances from personal finances, and planning the use of working capital more effectively. This activity had a positive impact on increasing the partner’s knowledge and awareness regarding business financial management. With this improved understanding, MSMEs are expected to implement better cash and working capital management practices to support sustainable business growth and development.